The Relationship between Physical Activity, Physical Fitness, Cognition, and Academic Outcomes in School-Aged Latino Children: A Scoping Review - J. P. Marrero-Rivera; Olivia Sobkowiak; Aimee Sgourakis Jenkins; Stefano J. Bagnato; Christopher E. Kline; Benjamin DH Gordon; Sharon E. Taverno Ross (MDPI AG, 2024)
This scoping review provides an overview of the relationship between physical activity, physical fitness, cognition, and academic outcomes in Latino school-aged children and identifies areas for future research. A primary search was conducted in PubMed, PsycINFO, Web of Science, and ERIC for original-research articles meeting the inclusion criteria; the search results were uploaded into PICO Portal and assessed by two independent reviewers. Of the 488 initial search results, 50 articles were eligible for full-text review, and 38 were included in this review. Most studies were cross-sectional, conducted in the United States or Chile, and included children 5-18 years old. Overall, the majority of articles reported positive associations between physical activity or physical fitness and cognitive outcomes (n = 11/12; 91.7%), and physical activity or physical fitness and academic outcomes (n = 22/28; 78.6%). In sum, this review provided consistent evidence for higher amounts of physical activity and greater physical fitness to be associated with various positive cognitive and academic outcomes in a school-aged Latino population. This scoping review also elucidated a substantial gap in the research regarding study design, with a discernible lack of interventional efforts. Future studies should test physical activity interventional strategies to optimize cognitive and academic outcomes in school-aged Latino populations.